Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

Use the Binomial Theorem to expand each binomial (5x-4y)^3

Sagot :

You should know that:

(a+b)(a+b)(a+b)

=a(a+b)(a+b)+b(a+b)(a+b)

=a(a²+2ab+b²)+b(a²+2ab+b²)

=a³+2a²b+ab²+a²b+2ab²+b³

=a³+3a²b+3ab²+b³

-----------------

If a=5x and b=-4y

(5x+(-4y))³

=(5x-4y)³

=(5x)³+3(5x)²(-4y)+3(5x)(-4y)²+(-4y)³

=125x³+3(25x²)(-4y)+15x(16y²)-64y³

=125x³+75x²(-4y)+240xy²-64y³

=125x³-300x²y+240xy²-64y³